A comparative analysis of competitive priorities and business performance between manufacturing and service firms. Issue 7 (11th September 2017) - Bouranta, Nancy; Psomas, Evangelos
Abstract : Purpose: The purpose of this paper is to investigate and contrast the levels of focus on competitive priorities (CPs) between service and manufacturing firms in Greece during an economic crisis and the influence of those CPs on business performance. Design/methodology/approach: Empirical data were collected from 298 company representatives of Greek firms with an approximately equal proportion of the firms being from the manufacturing ( n =157) and service ( n =141) industries. Exploratory and confirmatory factor analyses were conducted to validate the proposed first-order latent constructs as well as to determine the second-order latent construct (CPs). The CPs were employed to represent the hypothetical structural relationship of business performance. The fit and predictive accuracy of the model was estimated using AMOS software. Findings: The proposed CPs model consists of five latent constructs: quality, delivery, cost, innovation, and customer focus. It was also verified regardless of industry (manufacturing or service) that the same set of CPs was used. However, these two sectors differed on the emphasis they paid to the selected CPs. Originality/value: The major contributions of the paper are fourfold. First, this study represents the first empirical investigation, to the best of the authors' knowledge, into CP issues in the service and manufacturing industries, to determine whether there are differences in CPs between these two sectors. Second, the paper focused on the operations strategy of service enterprises in a field where the empirical evidence remains scarce. Third, the current research is conducted in a developing country with economic problems and political instability, while previous empirical research was mainly conducted in large and highly industrialized countries. Knowing about the Greek economy's economic crisis and the CPs of different industries within it provides a unique and interesting perspective to this research. Finally, the findings introduced a set of common CPs as being applicable to both sectors (services and manufacturing), as the number and the nature of its dimensions seems to be independent of the type of sector examined.